Comparison Of Lean Warehouse Implementation In Several Companies In Indonesia - Malini Lubis, Fatimah; Juanda Simatupang, Teddy; Listanti, Virginia; Listya Azhari, Paramitha (Best Journal of Administration and Management, 2023)
When implementing the lean philosophy in the warehouse, there are environment issues or aspects to be considered. This study use literature research review by reviewing journals which specifically research on the implementation of lean warehousing in companies in Indonesia. Identification of waste and its investigation to find the causes is important to have the right recommendation for improvement can be compared between companies. Ideas for improvement such as using labels to segregate used and unused materials or tools is an example of sorting. Arranging lay out, racks and bins, and materials to become neat and tidy, easy to find, and clean is a must have properties for a warehouse. Updated policies and procedures are required for standardization of work. To sustain the implementation result, it is important to have training, knowledge sharing or other similar and creative events. Leadership, measuring, and the driving of improvements are key roles for the success of implementation